ANALISIS KELAYAKAN USAHA BUDIDAYA IKAN NILA (Oreochromis niloticus) KERAMBA JARING APUNG DI KABUPATEN SERUYAN KALIMANTAN TENGAH - Bahruddin Yusuf; Emmy Sri Mahreda; Erma Agusliani (Universitas Lambung Mangkurat, 2022)
Seruyan Regency with the capital Kuala Pembuang is one of the regencies in Central Kalimantan Province, some of its people live in coastal areas and manage fishery resources so that the marine and fishery sector is the mainstay and is very interested in utilizing marine and fishery resources in a sustainable manner. The aim of the study was to analyze the feasibility of tilapia (Oreochromis niloticus) floating net cages cultivation in the Seriyan district of Central Kalimantan. The location of the sampling was done purposively. The feasibility of investing in tilapia cages in the Seriyan district is calculated using the investment criteria which include Net Present Value (NPV), Net Benefit Ratio (NBCR), and Internal Rate of Return (IRR). The results of the analysis of the financial feasibility of tilapia cage business from 3 (three) managers were declared to have met the business feasibility criteria in 3 (three) research periods. This can be seen from the Net Present Value which has a positive value and the Internal Rate of Return which is greater than the required interest rate. The results of the sensitivity analysis with the scenario if there is an increase in operational costs by 10%, 20% and 30%, it is stated that the tilapia fish cage business from the three managers does not meet the business feasibility criteria. The results of the sensitivity analysis with the scenario if there is an increase in operational costs and a decrease in income by 10%, 20% and 30% respectively, it is stated that the tilapia fish cage business from the three managers does not meet the business feasibility criteria.